Expression of haematopoietic stem cell markers, CD133 and CD34 on human corneal keratocytes. Issue 1 (6th September 2006) - Perrella, G; Brusini, P; Spelat, R; Hossain, P; Hopkinson, A; Dua, H S
Abstract : Aim: To study the expression of CD133 and CD34 antigens on cultured human keratocytes over time. Methods: Primary cultures of human corneal stromal cells were established from explants derived from cadaver eye donors. The cultures were sorted for CD133+ and CD34+ cells using magnetic beads. Both the primary cultures and secondary passages of sorted cells were further analysed by flow cytometry and western blot analysis for expression of the same antigens over time. Results: Four different cell populations—namely, CD133+, CD133−, CD34+ and CD34−, were identified in the culture samples. Two further specific subgroups were identified by flow cytometry: CD133+/CD34− cells and CD133+/CD34+ cells. Expression of CD133 declines more than CD34 with time in cell cultures. Although most cells lost expression of these markers, small populations retained staining up to 5 weeks in culture. Conclusion: Human keratocytes express the haematopoietic stem cell markers CD133 and CD34. This expression decreases with time in culture, with most but not all cells losing expression. On the basis of these markers, the corneal stroma shows a heterogeneous population of cells. Expression or down regulation of expression of these molecules could represent different stages of activation of these cells.